Ergonomic risks in university engineering students during the pandemic - Tupayachy-Quispe, Danny; Almirón, Jonathan; Castillo-Barriga, Ana; Aguilar-Gordillo, Sarlet; Acevedo-Obando, Grace; Ortiz-Valdivia, Yosheff (LACCEI, 2024)
The objective of this research work was to determine the existence of ergonomic risks in students, who carried out their studies in virtual mode in Industrial Engineering at the Catholic University of Santa María. It was carried out through surveys, observation and the application of the ROSA methodology. The results determine that the students' performance was not optimal, with different causes being psychosocial factors such as stress, anxiety and fatigue; as well as physical factors such as musculoskeletal disorders developed by a sedentary lifestyle, academic load, workplace conditions, lack of physical activity and others.